Series-Fed Printed Dipole Array Incorporated with Linear to Circular Polarization Metasurface Converter - Nkimbeng, Cho Hilary Scott; Park, Ikmo (GSMM 2022 - 14th Global Symposium on Millimeter-Waves and Terahertz, 2022)
In this paper, the design of a series-fed angled dipole array antenna incorporated with a polarization conversion metasurface is presented. The antenna consists of a two-layer cascaded metasurface made of 4×4 circular patches with cross-slots of unequal lengths placed above the series-fed angled dipole array antenna in the end-fire direction with an air gap. The series-fed angled dipole array antenna consists of eight dipole elements with equal spacing, and each dipole was connected to a parallel stripline printed on the front and backsides of the substrate. The metasurface made of a circular patch with cross-slots of unequal lengths is used for polarization conversion of the linearly polarized wave to the circularly polarized wave. The measured reflection coefficient for |S11| < -10 dB results yield an impedance bandwidth of 26.2 to 31.4 GHz (18.0%), a 3-dB axial ratio (AR) bandwidth of 26.5 to 31.2 GHz (16.3%), a 3-dB gain bandwidth of 26.2 - 30.5 GHz (15.16%) with a peak gain of 10.9 dBic, and radiation efficiency of more than 80% within the AR bandwidth.
Keywords: Array-antenna; Dipole arrays; End-fire array; Endfire array antenna; Metasurface; Polarization conversion; Polarization conversion surface.; Printed dipole; Printed dipole array antenna; circular polarization; endfire array antenna; metasurface; polarization conversion surface.; printed dipole array antenna